Molecular epidemiology and antimicrobial resistance profiles of Pseudomonas aeruginosa causing bloodstream infections in neutropenic cancer patients - Cadenas-Jiménez, Irene; Badía-Tejero, Ana María; López-Causapé, Carla; Morosini, María-Isabel; Portillo-Calderón, Inés; Machado, Marina; Larrosa, Nieves; Dávila, Piluca Martín; Palacios-Baena, Zaira; Puig-Albasanz, Adaia; Tubau, Fe; Oliver, Antonio; et al. (Frontiers in Microbiology, 2025)
BackgroundBloodstream infections (BSI) in neutropenic cancer patients, particularly those caused by Pseudomonas aeruginosa (PA), are associated with high morbidity and mortality. The increasing prevalence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) PA strains complicates clinical management. This study aimed to characterise PA strains causing BSI in neutropenic cancer patients and assess the association between microbiological features and clinical outcomes.MethodsWe analysed PA strains from 94 BSI episodes in neutropenic cancer patients across five Spanish hospitals (2006–2018). Antimicrobial resistance, alginate and pigment production were assessed. Whole-genome sequencing was performed to identify resistance mutations and virulence genes.ResultsPA strains exhibited high genetic diversity, with ST175 as the most prevalent clone (28.7%). MDR non-XDR and XDR strains accounted for 10.3% and 18.1% of cases, respectively. The highest resistance rates were for ciprofloxacin (42.6%) and imipenem (36.2%). Resistance was primarily driven by chromosomal mutations. ExoU was present in 24.4% of strains, associated with serotype O11 and ST253. Seven-day and 30-day mortality were 21.3% and 31.9%, respectively. Mortality was not significantly influenced by resistance phenotypes or the presence of ExoU. Polymicrobial infection (p = 0.016), septic shock (p < 0.001), Intensive Care Unit admission (p = 0.002), and inadequate empirical antibiotic therapy (p = 0.002), were linked to increased 7-day mortality.ConclusionST175 was the dominant high-risk clone, associated with antimicrobial resistance, while virulence traits were more common in susceptible strains. Inadequate empirical antibiotic therapy and septic shock significantly impacted early 7-day mortality, underscoring the need for early diagnosis and optimised treatment strategies.